2009
DOI: 10.1007/s00425-009-0984-5
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous nitric oxide enhances cadmium tolerance of rice by increasing pectin and hemicellulose contents in root cell wall

Abstract: To study the mechanisms of exogenous NO contribution to alleviate the cadmium (Cd) toxicity in rice (Oryza sativa), rice plantlets subjected to 0.2-mM CdCl(2) exposure were treated with different concentrations of sodium nitroprusside (SNP, a NO donor), and Cd toxicity was evaluated by the decreases in plant length, biomass production and chlorophyll content. The results indicated that 0.1 mM SNP alleviated Cd toxicity most obviously. Atomic absorption spectrometry and fluorescence localization showed that tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
159
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(183 citation statements)
references
References 52 publications
9
159
1
3
Order By: Relevance
“…Pectin has been demonstrated to be a key intermediate material in cell-wall P re-utilization, and it responds to multiple environmental stimuli. For instance, Yang et al (2008) and Xiong et al (2009) found that exposure of rice to Al and Cd led to an increment of pectin content in root. Yang et al (2010) reported that osmotic stress inhibited Al accumulation in root apices of the Al-sensitive genotype VAX1, an effect that was attributed to a lower cell-wall pectin content and its degree of methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Pectin has been demonstrated to be a key intermediate material in cell-wall P re-utilization, and it responds to multiple environmental stimuli. For instance, Yang et al (2008) and Xiong et al (2009) found that exposure of rice to Al and Cd led to an increment of pectin content in root. Yang et al (2010) reported that osmotic stress inhibited Al accumulation in root apices of the Al-sensitive genotype VAX1, an effect that was attributed to a lower cell-wall pectin content and its degree of methylation.…”
Section: Discussionmentioning
confidence: 99%
“…39 Xiong et al concluded that decreased distribution of cadmium in the soluble fraction of leaves and roots and increased distribution of cadmium in the cell walls of roots were responsible for the nitrogen monoxide-induced increase of cadmium tolerance in rice. 40 Excessive lignin production induced by cadmium accounted for the solidification of cell wall and subsequent restriction of root growth. 41 The distribution of de-esterified and esterified pectins on the radical apex differed with different concentrations of cadmium, indicating that cadmium spatially modulates the synthesis and distribution of both pectins.…”
Section: Cadmium and Cell Wall Constructionmentioning
confidence: 99%
“…Lead can be identified by optical microscopy, e.g., by rhodizonic acid that forms red complexes with this metal (Tung and Temple 1996). Cadmium may be identified, e.g., by Leadmium reagent (Xiong et al 2009) in fluorescence and confocal microscopy. Aluminum is often stained with, e.g., morin (unbound, free Al ions; Eticha et al 2005a) and lumogallion (Silva et al 2000), the fluorochromes also used for fluorescence and confocal microscopy.…”
Section: Detection Of Tms In Plant Cell Wallmentioning
confidence: 99%